The Morphology and Clinical Significance of the Extraforaminal Ligaments at the Cervical Level. Issue 1 (1st January 2015) - Shi, Benchao; Zheng, Xuefeng; Zhang, Hui; Sun, Chao; Cao, Yanlin; Jin, Anmin; Ding, Zihai
<x xml:space="preserve">Abstract</x> Study Design. A dissection-based study of 6 embalmed cadavers. Objective. To identify and describe the extraforaminal ligaments (EFLs) in relation to the area of the cervical intervertebral foramina and to evaluate their clinical significance. Summary of Background Data. EFLs between the lumbar spinal nerves and the tissues surrounding the intervertebral foramens have been well established. However, research work has been undertaken to describe the local anatomy of the extraforaminal part of the cervical spine; detailed anatomic studies of the EFLs of cervical nerves have not been performed. Methods. One hundred ninety-six cervical intervertebral foramina from 6 adult embalmed cadavers were studied, and the existence and type of the EFLs were identified. The morphology, quantity, origin, insertion, and the spatial orientation of the EFLs in the cervical region were observed, and the length, width, or diameter and thickness of the ligaments were measured with a vernier caliper. Results. The EFLs could be found from the second cervical to the first thoracic spinal nerve. These ligaments could be divided into 2 types: radiating ligaments, which connected the nerve root sleeves that radiated to the transverse processes, the wall of the intervertebral foramina, and even the adjacent nerve root through the small transverse foramen; transforaminal ligaments, which originated from the anteroinferior margin of cranial transverse process and inserts in the superior margin of the anterior tubercle of caudal transverse process crossing the spinal nerve ventrally. Conclusion. Between the cervical spinal nerves and nearby structures, there are 2 types of the EFLs. The radiating ligaments may serve as a protective mechanism against traction and play an important role in the positioning of the nerves in the intervertebral foramen. However, in all probability, the transforaminal ligaments may be the underlying cause of the cervical radiculopathy. Level of Evidence: 4